Gesundheitsfürsorge bei deutschen Auswanderinnen und Auswanderern in die USA - Schweig, Nicole (Österreichische Zeitschrift für Geschichtswissenschaften, 2011)
At the beginning of the 19th century a strong migration wave from German territories to the US began. Bad economic conditions and the entire lack of prospects for the future were common, but the individual motifs and reasons of the emigrants were manifold, though. Men and women emigrated under different circumstances. Some were individuals who set out on their own, others travelled in groups starting from a certain village or town in Germany. After arriving in the US, the emigrants stayed in close contact and created ethnic communities. In their letters home they convinced some of their relatives to follow them; ‘chain migration’ came under way. Individuals and families already living in the US welcomed newly arrived relatives and sup- ported them. At the other hand, younger emigrants left their family of origin behind, thus losing important social support in case of unemployment or illness. The article focuses on the measures female and male migrants took to stay or become healthy during and short after migration. Furthermore, it examines how the social networks of the emigrants became widened by marriages and how efficient they were in respect to health care and coping with illness.